2017
DOI: 10.1016/j.eurpolymj.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial PHAs coating for titanium implants

Abstract: Biomaterial-associated infection is a serious complication of modern implantation surgery.Thus, the improvement of implant surfaces is required to avoid the first stage for biofilm formation, bacterial adhesion. The current research addresses this issue by developing drug delivery systems (DDS) consisting of antibiotic-loaded polyhydroxyalkanoates (PHAs) coatings on titanium implants. Dip-coating technique was used to achieve optimal coatings with biodegradable biopolyesters, polyhydroxybutyrate (PHB) and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
(39 reference statements)
1
28
0
Order By: Relevance
“…Because of its bio‐degradability, the PHB long‐chain polymer also has been a focus of research interest in biomedical disciplines, including controlled drug delivery, surgical structure, wound dressing, vascular graft, blood vessel, orthopedic devices, tissue engineering, and skin substitutes . To date, studies on the antibacterial properties of PHB have involved PHB with the addition of other antibacterial agents or with chemically grafted antimicrobial moieties …”
Section: Methodsmentioning
confidence: 99%
“…Because of its bio‐degradability, the PHB long‐chain polymer also has been a focus of research interest in biomedical disciplines, including controlled drug delivery, surgical structure, wound dressing, vascular graft, blood vessel, orthopedic devices, tissue engineering, and skin substitutes . To date, studies on the antibacterial properties of PHB have involved PHB with the addition of other antibacterial agents or with chemically grafted antimicrobial moieties …”
Section: Methodsmentioning
confidence: 99%
“…PHB and its copolymer P(3HB-3HHx) sheets loaded with lysozyme are being used for biofilm inhibition and in fabrication of wound dressing [89]. Implants coated with PHB copolymer fastens the degradation process for a stable drug release within a given time period as compared to its co-polymer [90,91].…”
Section: Medical Devicesmentioning
confidence: 99%
“…Several authors have reported the effect of clay nanoparticles in the processing and mechanical properties of nanocomposites based on EPDM/Polyolefin blends, using various types of compatibilizers . On the other hand, microbial contamination has increasingly threatened human health with the increasing appearance of antibiotic resistance bacteria . Bacteria and fungi are able to form a microbial biofilm, which can damage the human health with pathogenic effects such as allergies or infections.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] On the other hand, microbial contamination has increasingly threatened human health with the increasing appearance of antibiotic resistance bacteria. 7,8 Bacteria and fungi are able to form a microbial biofilm, which can damage the human health with pathogenic effects such as allergies or infections. Polymeric materials for medical applications often require antibacterial properties, which have been achieved by the incorporation of particles with antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%